2009
DOI: 10.1111/j.1750-3841.2009.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes on Enological Parameters of White Wine Packaged in Bag‐in‐Box during Secondary Shelf Life

Abstract: This study investigated the effects of temperature (22, 35, and 45 degrees C), storage time (48, 30, and 15 d), and packaging type on the quality of white wine in bag-in-box (BIB) during the secondary shelf life. Several enological parameters (color and contents of free and total SO2, total aldehyde, and total phenol) were monitored and correlated with oxygen transmission rate (OTR) and Fourier transform infrared (FTIR) spectral data. Time and temperature had significant effects on color development and SO2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Recent studies have shown that FTIR‐based methods have been successfully applied in the food industry, in association with food quality evaluation (Woodcock and others 2008; Fu and others 2009; Subramanian and others 2009; Wang and others 2010; Rodriguez‐Saona and Allendorf 2011), with a few applications focusing on roasted coffee (Lyman and others 2003; Wang and others 2009; Ribeiro and others 2010). FTIR‐based methods are fast, reliable, simple to perform, and do not require sample pretreatment, with the sampling/analysis procedure usually taking less than 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that FTIR‐based methods have been successfully applied in the food industry, in association with food quality evaluation (Woodcock and others 2008; Fu and others 2009; Subramanian and others 2009; Wang and others 2010; Rodriguez‐Saona and Allendorf 2011), with a few applications focusing on roasted coffee (Lyman and others 2003; Wang and others 2009; Ribeiro and others 2010). FTIR‐based methods are fast, reliable, simple to perform, and do not require sample pretreatment, with the sampling/analysis procedure usually taking less than 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increase in concentration of long-chain esters and the decrease of acetates, such as isoamyl acetate, isopentyl acetate and 2-phenylethyl acetate, have been demonstrated (González-Viñas et al, 1996;CejudoBastante et al, 2011). In general, however, the concentration of most of the wine volatile compounds decreases after one year of bottle storage (Cejudo-Bastante et al, 2011), and the major parameters influencing the rate of volatile change in concentration during ageing are temperature (Leino et al, 1993;De la Presa-Owens & Noble, 1997;Bueno et al, 2010;Robinson et al, 2010;Recamales et al, 2011;Butzke et al, 2012; and wine packaging materials (Fu et al, 2009;Mentana et al, 2009;Ghidossi et al, 2012;Hopfer et al, 2012). Research done on aroma evolution has been directed mainly at non-aromatic grapes (Airen, Chardonnay, Riesling, Sauvignon blanc), while little information is present on wine produced from aromatic grapes such as Muscat and Malvasia (Pérez-Magariño et al, 2013).…”
Section: Effect Of Bottle Storage On White Winesmentioning
confidence: 99%
“…During the secondary shelf‐life storage (i.e., after opening the package), oxidation was likely the major reaction that occurred in the BIB white wines as a result of temperature abuse and increased oxygen ingress through the package. Also, the OTR of the BIB inner bag liner was previously found to increase with increasing storage temperature . Therefore, the observed enhanced separation of groupings at higher temperatures could be at least partly related to the increased rate and extent of oxidation.…”
Section: Resultsmentioning
confidence: 82%
“…At each sampling time when wines were sampled for GC analysis, additional aliquots of approximately 140 mL were collected and immediately analyzed for the related enological parameters (A 420 , free SO 2 , total SO 2 , total phenol, and total aldehyde). Folowing the procedure as reported previously , A 420 values were determined using a spectrophotometer, free and total SO 2 were determined using the Ripper titration method, total phenol was obtained using the Folin–Ciocalteau micro‐method, and total aldehyde was measured using 3‐methyl‐2‐benzothiazolinone hydrazone hydrochloride reagent. The standard error of the laboratory (SEL), defined as the standard error of variance between the samples analyzed by the analytical methods, was estimated by evaluating all the investigated samples by using the following equation : SEL=i=1n0.12em[]j=1m()XijXi2/m1nwhere X ij is the value of j th replicate for an i th sample, X i is the mean value of all replicates for an i th sample, m is the number of replicates, and n is the number of samples.…”
Section: Methodsmentioning
confidence: 99%